Development of Android -Based Ambulance Tracking Prototype on the SPGDT Module of the Special Region of Yogyakarta - Nugroho, Dwi (Jurnal Sistem Informasi Kesehatan Masyarakat, 2023)
Background: An emergency is a dangerous situation that takes place suddenly. In the case of an emergency, response time is needed. Several factors contributed to the long response time for handling, especially the ambulance response to emergency cases, namely accessibility, accommodation, and availability of supporting facilities. To improve access and quality of emergency services and speed up response time, the Government of Indonesia issued the SPGDT service. The use of the SPGDT in the Special Region of Yogyakarta still needs an ambulance tracking service. Hence, people are worried about the arrival of an ambulance service in response to an emergency. This study aims to develop ambulance tracking services in the SPGDT Yogyakarta Special Region module. Methods: This research is qualitative research with an action research design. The stages in action research consist of diagnosing, planning, action, and evaluation. Results: The results of this study, at the diagnostic stage, resulted in the need for call center users to record and report on the SPGDT Website while the need for ambulance drivers to track ambulances. At the planning stage, it produces a data flow that will make. At the action stage, create a design consisting of flow chart diagrams, data flow diagrams, entity relationship diagrams, wireframes, and user interface designs. At the evaluation stage, the final score for the prototype was produced using the System Usability Scale (SUS) questionnaire, with the final score for recording and reporting getting a final score of 72, while in the evaluation of ambulance tracking for drivers, a final score of 80.Conclusions: Improved recording and reporting of emergency events and ambulance tracking after being developed and tested with the SUS questionnaire. Include the prototype in the "acceptable" category. With an acceptable interpretation, it is considered successful in being designed to meet user needs and is optimally utilized to assist in handling emergency cases.